Seroprevalence rates of BKV, JCV, and MCPyV polyomaviruses in the general Czech Republic population - Sroller, Vojtěch; Hamšíková, Eva; Ludvíková, Viera; Vochozková, Petra; Kojzarová, Martina; Fraiberk, Martin; Saláková, Martina; Morávková, Alena; Forstová, Jitka; Němečková, Sárka (Journal of medical virology, 2014)
JC and BK polyomaviruses (JCV and BKV) infect humans and can cause severe illnesses in immunocompromised patients. Merkel cell polyomavirus (MCPyV) can be found in skin carcinomas. In this study, we assessed the occurrence of serum antibodies against MCPyV, BKV, and JCV polyomaviruses in a healthy population of the Czech Republic. Serum samples from 991 healthy individuals (age range: 6-64 years) were examined by enzyme-linked immunoassay (ELISA) using virus-like particles (VLPs) based on the major VP1 capsid proteins of these viruses. Overall, serum antibodies against MCPyV, JCV, and BKV were found in 63%, 57%, and 69%, respectively, of this population. For all three viruses, these rates were associated with age; the occurrence of antibodies against MCPyV and JCV was highest for those older than 59 years, while the occurrence of antibodies against BKV was highest in those aged 10-19 years and 20-29 years. This is the first large study to determine the seroprevalence rates for BKV, JCV, and MCPyV polyomaviruses in the general Czech Republic population.
Keywords: myši inbrední ICR; buněčné linie; mladiství; lidé; Adult; Middle Aged; BK Virus; Case-Control Studies; Age Distribution; Infant; Female; Cell Line; dítě; Merkel cell polyomavirus; Polyomavirus Infections; Tumor Virus Infections; Adolescent; Humans; infekce onkogenními viry; Antibodies, Viral; studie případů a kontrol; virus JC; Česká republika; předškolní dítě; lidé středního věku; Child, Preschool; séroepidemiologické studie; věkové rozložení; mužské pohlaví; mladý dospělý; zvířata; Czech Republic; ženské pohlaví; polyomavirové infekce; Young Adult; Animals; protilátky virové; Male; Merkelův polyomavirus; virus BK; dospělí; Child; JC Virus; Seroepidemiologic Studies; Mice, Inbred ICR; kojenec